1995
DOI: 10.1159/000236918
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn from the Allergic Zoo?

Abstract: Several animal species, in particular dogs, cats and horses spontaneously develop IgE-mediated allergic diseases. They can also be experimentally sensitized. Comparative veterinary allergology is increasingly providing valuable information in allergy research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…House dust is also an important environmental allergen in humans and other animals [4,7], and is the most common allergen associated with canine AD [14,15]. However, there is no standardization for the production of house dust extract components among companies that manufacture allergens for laboratory purposes.…”
Section: Discussionmentioning
confidence: 99%
“…House dust is also an important environmental allergen in humans and other animals [4,7], and is the most common allergen associated with canine AD [14,15]. However, there is no standardization for the production of house dust extract components among companies that manufacture allergens for laboratory purposes.…”
Section: Discussionmentioning
confidence: 99%
“…2 Similarly, in dogs, there is no clear evidence that atopic dermatitis is inherited, although a strong breed predilection has been reported in Labrador and Golden Retrievers. 3,4 In addition, results of a breeding study by Schwartzman 5 indicated that certain charac-teristics of atopic disease were seen in the offspring of atopic parents, and de Weck 6 reported that Beagles could be classified as either high or low IgE responders and demonstrated that IgE concentrations were controlled by genetics.…”
mentioning
confidence: 99%
“…In recent years, the number of patients with allergic diseases has been increasing in dogs as well as in humans [2,5,7,10,20]. Immunogloblin E (IgE) antibodies play an important role in the development of immediate hypersensitivity (type I allergic disease) [7,10,20].…”
mentioning
confidence: 99%